Characterization of cryptovirogenic, virus-productive and helper-dependent virogenic hamster tumour cell lines - Geryk, J; Sainerová, H; Sovová, V; Svoboda, J (Folia biologica, 1984)
Three hamster cell lines were established from tumours induced with the virus rescued from XC cells. The H-20 cell line produces little infectious transforming virus and synthesizes uncleaved Pr76 (product of gag gene) in the amount comparable to that obtained from PR-RSV-C-infected permissive cells. Like the helper-dependent virogenic H-18 cell line, it however produces only a marginal amount of viral glycoprotein (env gene product) as revealed by the complementation assay. Even a lower amount of the env gene product almost escaping detection by the complementation test has been found in the helper-dependent virogenic H-18 cell line. This cell line has also been shown to produce a low quantity of the gag gene product. The H-19 cell line synthesizes no detectable gag or env gene products and is not inducible by cell fusion with chicken fibroblasts even when preinfected with the replication competent td PR-C. This is in agreement with data from restriction analysis (Svoboda et al. 1983) showing that H-19 cells contain only cryptic proviral sequences represented by v-src and LTR. The three cell lines together with those described previously (Svoboda 1981) were analysed karyologically. Random changes in chromosome numbers and structural alterations in individual chromosomes were only found.
Keywords: virová transformace buněk; Cell Line; replikace viru; virové proteiny; chromozomální aberace; Sarcoma, Avian; Helper Viruses; viry ptačího sarkomu; Cell Transformation, Viral; Viral Proteins; Avian Sarcoma Viruses; Cricetinae; Chromosome Aberrations; Animals; Virus Replication; zvířata; buněčné linie; ptačí sarkom; pomocné viry; virové geny; Genes, Viral; křečci praví